Assessing the impact of voluntary certification schemes on future sustainable coffee production - Jones, Katharine; Njeru, Ezekiel Mugendi; Garnett, Kenisha; Girkin, Nicholas T. (MDPI, 2024)
Coffee production faces major sustainability issues and consumers increasingly look to choose certified coffee as awareness grows. While consumers’ understanding of sustainability issues is limited, independent voluntary certification schemes such as Fairtrade, Rainforest Alliance, and certified organic—three high-profile schemes—can play a role in future-proofing coffee production through standard-setting. These schemes can also inform consumers about sustainability issues from economic, environmental, and social perspectives, thus driving up demand for sustainably grown coffee, and supporting an enabling environment for farmers and coffee-producing countries to improve the status quo. Sustainably grown coffee ensures that farmers sustain production while protecting the environment and the income that farmers rely on to maintain their livelihood. Based on a thematic analysis and synthesis of previous studies, this paper examines the social, economic, and environmental effects of voluntary certification schemes for coffee production. It evaluates the current state of coffee production and explores how certification schemes can be effective in encouraging more sustainable practices among producers. Three major voluntary certification schemes are evaluated to identify the impacts on producers, including key barriers and enablers to comply with sustainability standards and to determine how fit-for-purpose certification schemes are in assuring future sustainable coffee production.
Keywords: certification; fairtrade; rainforest alliance; organic; arabica; robusta